Assessment of Healthcare Waste Generated by Government Hospital in Agra City, India - Khajuria, A; Kumar, A (Our Nature, 2008)
Health care wastes include anatomical, pathological and clinical infectious/ hazardous organic and inorganic waste. The waste is disposed off in unscientific manner. The study has been conducted in the government health care establishment only to reveal the per day waste generation on each patient, present mode of waste management within the units bed, our suggestions which have helped the units to improve their waste management practices, in the city of Agra. Keywords: Waste management, Health scare waste, Management, Government hospital doi:10.3126/on.v5i1.794 Our Nature (2007)5:25-30